Early Childhood Educators’ Attitude toward STEAM and Online Learning as 21-st Century Skills - Jovanka, Della Raymena; Sumantri, M Syarif; Dhieni, Nurbiana; Karnadi, Karnadi (Indonesian Journal of Early Childhood Education Studies, 2021)
Mastery of 21st-century skills by teachers, such as integrating STEAM in daily learning through online learning in the globalization era, is necessary. These skills can be acquired through online learning. Currently, online learning is the primary alternative for implementing learning in the era of globalization, especially during the COVID-19 pandemic. However, do all teachers understand the importance of mastering 21st-century skills through online learning and how to conduct this online learning effectively? This study describes the teacher’s attitude towards online learning. The research method used is a survey in the form of a questionnaire distributed to 149 teachers spread throughout Indonesia. Participants in this study were students in open and distance learning systems. The study results indicate that teachers already understand online learning, can access and use all online learning resources provided by the campus for their learning purposes. This result can be seen from the number of their access to each type of online learning service. The implication of this research is to become an evaluation and reference material for education providers, especially distance learning systems, to improve the quality of services and learning materials according to the demands and developments of technology. Keywords: early childhood educator, online learning, attitude, open educational resources